2017
DOI: 10.1371/journal.pone.0170313
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-Clinical Safety Evaluation of SBP (HBsAg-Binding Protein) Adjuvant for Hepatitis B Vaccine

Abstract: Although adjuvants are a common component of many vaccines, there are few adjuvants licensed for use in humans due to concerns about their toxic effects. There is a need to develop new and safe adjuvants, because some existing vaccines have low immunogenicity among certain patient groups. In this study, SBP, a hepatitis B surface antigen binding protein that was discovered through screening a human liver cDNA expression library, was introduced into hepatitis B vaccine. A good laboratory practice, non-clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Figure 3 (Additional file 1 : Table S6) indicates that there is no significant ( p > 0.05) increase across all the treatment groups on day 14 (after the primer dose). This is in consonance with the works of Wang et al [ 42 ], which showed a slow IgG production after the first immunization. Day 21 (7 days after the first booster dose indicated a significant ( p < 0.05) increase when 2DHBV + ESM immunized mice were compared to mice immunized with the Hepatitis B vaccine.…”
Section: Discussionsupporting
confidence: 92%
“…Figure 3 (Additional file 1 : Table S6) indicates that there is no significant ( p > 0.05) increase across all the treatment groups on day 14 (after the primer dose). This is in consonance with the works of Wang et al [ 42 ], which showed a slow IgG production after the first immunization. Day 21 (7 days after the first booster dose indicated a significant ( p < 0.05) increase when 2DHBV + ESM immunized mice were compared to mice immunized with the Hepatitis B vaccine.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, HBsAg likely regulates NK cells during CHB infection by inhibiting STAT3 dimerization, nuclear translocation, or DNA binding. The secreted protein SBP and mitochondrial protein ECHS1 have been previously reported to be the binding proteins of HBsAg, but the NK cell membrane binding protein(s) of HBsAg remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%